Pemahaman Mahasiswa terhadap Konsep Gerak Benda di Bidang Miring dalam Mata Kuliah Fisika Dasar - Adelyna Oktavia Nasution; Salsabilla Khairus Syifa; Ramzi Azizan; Zein Rasyid Raditya Ananda (Pusat riset dan Inovasi Nasional, 2025)
Students' understanding of the concept of motion of objects on inclined planes still shows obstacles, especially when applied in real practice. This study aims to see the extent to which students understand the concept through simple experiments and questionnaires. The main focus of the study was on the results of the practicum, where the block slid faster on a smooth plane (an average of 1.25 seconds) than on a rough plane (an average of 1.61 seconds). This time difference reflects the effect of friction on the motion of objects, but some students were unable to explain the difference correctly. This indicates that there are still misconceptions in understanding the concepts of force and motion. Meanwhile, the results of the questionnaire only reinforced that most students felt the need for direct practice to understand this material. Thus, a practice-based learning approach is very important to strengthen students' conceptual understanding in Basic Physics courses.